2018
DOI: 10.1186/s12871-018-0571-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient positions on perfusion index

Abstract: BackgroundThe optimal position for surgery is one in which the patient is provided the best possible surgical intervention and put at minimum risk. Different surgical positions may cause changes in tissue perfusion. This study investigates the relationship between surgical patient positions and perfusion index.MethodsA sample of 61 healthy individuals with no peripheral circulatory disorders, chronic diseases, or anemia was included in this study. Participants held six different positions: supine, prone, 45-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
1
31
1
Order By: Relevance
“…Increased intra-abdominal pressure in prone position contributes to subsequent physiological changes such as decreased cardiac index, inferior vena caval obstruction, and pulmonary ventilation/perfusion distribution [28]. It is reported that compared with the supine position, the prone position adversely affects the PI values [29]. In the present study, no significant differences in SpHb data were noted between the supine and prone positions in the same patient.…”
Section: Discussionmentioning
confidence: 40%
“…Increased intra-abdominal pressure in prone position contributes to subsequent physiological changes such as decreased cardiac index, inferior vena caval obstruction, and pulmonary ventilation/perfusion distribution [28]. It is reported that compared with the supine position, the prone position adversely affects the PI values [29]. In the present study, no significant differences in SpHb data were noted between the supine and prone positions in the same patient.…”
Section: Discussionmentioning
confidence: 40%
“…To take into account the postural, gravitationally induced effects on BP, it should be mentioned that the head-down Trendelenburg position leads to a temporary increase of venous return and preload, cardiac output and perfusion index [28]. Certainly, the stroke volume variation is subjected to the body posture [29,30], but the pressure hemodynamic effects, especially in people with hypotension, heart failure or aortic stenosis are the subject of dispute between various authors [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, parameters for evaluation of peripheral perfusion in the skin, including PPI, are increasingly being recommended as useful measures for body perfusion [19,20]. PPI is used as an indicator of peripheral perfusion in intensive care units [20,21] and operating theaters [4,22]. A recent study reported that monitoring PPI reflects changes in systemic hemodynamics during general anesthesia in a setting of changing preload conditions [4].…”
Section: Discussionmentioning
confidence: 99%